2021
DOI: 10.3389/fcell.2021.757168
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dec1-PPARγ Axis Impairs Proliferation and Apoptosis Homeostasis Under Hypoxia in Pulmonary Arterial Hypertension

Abstract: Background: The hypoxia-induced pro-proliferative and anti-apoptotic characteristics of pulmonary arterial endothelial cells (PAECs) play critical roles in pulmonary vascular remodeling and contribute to hypoxic pulmonary arterial hypertension (PAH) pathogenesis. However, the mechanism underlying this hypoxic disease has not been fully elucidated.Methods: Bioinformatics was adopted to screen out the key hypoxia-related genes in PAH. Gain- and loss-function assays were then performed to test the identified hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…10 In vitro observation showed an elevated proliferation and a declined apoptosis of pulmonary arterial endothelial cells under hypoxia conditions by the upregulation of Bhlhe40. 12 Conversely, our previous studies found a low expression in high glucose-treated VSMCs. 5 The reasons for this discrepancy might be due to the differences in cell types, handling of samples, and study design.…”
Section: Discussionmentioning
confidence: 70%
“…10 In vitro observation showed an elevated proliferation and a declined apoptosis of pulmonary arterial endothelial cells under hypoxia conditions by the upregulation of Bhlhe40. 12 Conversely, our previous studies found a low expression in high glucose-treated VSMCs. 5 The reasons for this discrepancy might be due to the differences in cell types, handling of samples, and study design.…”
Section: Discussionmentioning
confidence: 70%
“…The differentiated embryo chondrocyte expressed gene 1-peroxisome proliferative-activated receptor-γ axis has also been delineated as a critical element in hypoxia-modulated signaling, integral to the imbalance between proliferation and apoptosis in PAECs. This finding underscores the complexity of the cellular milieu in PH and the nuanced equilibrium required for vascular homeostasis (46).…”
Section: Role Of Apoptosis In Asmentioning
confidence: 70%
“…First, among all the OSA-disrupted clock genes, Dec1 shows the most prominent change and the most specific OSA effect in OSA patients during the morning ( Gaspar et al, 2021 ). Second, as a hypoxia-responsive and stress-associated protein, others and we have been found that Dec1 transcriptionally suppresses another transcriptional factor peroxisome proliferative activated receptor-γ (PPARγ), a key mediator in regulating insulin sensitivity ( Yun et al, 2002 ; Li et al, 2021 ). Third, interactions of both Dec1/PPARγ and Dec1/IL-6 occur under inflammatory or oxidative burden and involved in cellular energy metabolism ( Yun et al, 2002 ; Ning et al, 2017 ; Noshiro et al, 2020 ; Luan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%